Quantitative assessment and antibacterial activity of Origanum vulgare L. - Kumari, Priti; Joshi, Girish C; Tewari, Lalit M; Singh, Bibhesh K (Journal of Phytology, 2011)
Biodiversity, which twenty years ago was considered unimportant by most ecologists, has now been shown to impact significantly upon many aspects of ecosystem functioning. Diversity must now be added to the list of factors — including species composition, disturbance regime, soil type and climate — that influence ecosystem functioning. The recent knowledge of the importance of biodiversity highlights an under-appreciated truth — although society is dependent on natural and managed ecosystems for goods and services that are essential for human survival, we know all too little about how ecosystems work. Origanum vulgare L. is one of the important ethno medicinal plants, are found spread over to sub-temperate forest zone. They are of Ayurvedic importance and have trade value as well. Due to over exploitation and habitat degradation they are now turning into a rare species. Threat assessments of this species revealed that they are vulnerable in study area under reference. Their dominance too was found less as compare to other species. Their diversity profile in study areas also went down. Origanum vulgare L. has antimicrobial activities but Becillus subtillis, Pseudomonas aereuguinosa, Staphylococcus aureus and Escherchia coli bacteria were shown to be proactive. Due to fast growing urbanization of life, people are being attracted towards use of natural products and as such utility of such plants are gaining ground. Thus the need is to protect, promote and conserve such natural resources to have advantage of biodiversity conservation.